Code-Switching in The Youtube Video of Nessie Judges - Aji Arsidi, Dimas; Santi Indriani, Ketut; Puspitaning Adni, Nissa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research focused the code-switching that appeared in the video "ANATOLY: PSIKOPAT RUSIA yang OBSESI sama.... | #NERROR" by youtuber Nessie Judges. The purpose of this study was to determine the types of code-switching the reasons of code-switching was used in the video. The types were intra sentential code-switching, inter sentential code-switching, and tag switching. The theory applied in this study was Hoffman's theory, and the descriptive qualitative method used to collect the data, which included documentation and note taking. The result were eight data categorized into intra-sentential code switching, one data belonged to inter-sentential code switching, and four data in tag switching. Furthermore, the reason of using code-switching were talking about a specific topic, interjection, intention of clarifying the speech content for the interlocutor, and expressing group identity.